Observational Learning of Junior Residents During Surgery: Exploring Promoters and Barriers to Learning - Raîche, Isabelle (Université d'Ottawa / University of Ottawa, 2016)
Surgical observation is an integral part of surgical training. Junior residents, who have limited understanding of the procedure being performed, frequently engage in observation in order to gain exposure to surgical techniques. This limited experience, and the relative lack of guidance currently provided to them, might limit their ability to learn by observing. This thesis examines learners’ perceptions of the value of surgical observation, the barriers to learning in the surgical environment, and the factors that facilitate learning within the context of the operating room. An intervention, employing predefined objectives in the form of sets of questions, was introduced and the impacts of this intervention in terms of junior residents’ attitudes toward observation were explored. Two rounds of focus groups examined learners’ perceptions: one before introducing the intervention and one after it. Transcripts from these focus groups were analyzed using a qualitative interpretative approach and focus group participants provided considerable insight into observational learning. Many barriers were identified, including logistical constraints and lack of guidance. The surgical culture, within which observation is perceived as less effective than performing the surgery itself, was also mentioned as a factor that impedes learning during observation. Following the intervention, participants felt more validated as learners in the operating room and appreciated having clear objectives when observing procedures. Participants did mention that their busy clinical obligations would likely limit their use of any educational intervention. It was also noted that interventions to promote learning through observation would have to be fully supported by their program to be used on a regular basis. In conclusion, many factors that impact learning during surgical observation were identified. While trainees felt that increased guidance for observation was helpful, the environment in which learning takes place would have to be optimized to facilitate junior trainees’ learning.
Keywords: Surgical observation; Junior residents; Apprenticeship; Instruction